Turmeric Dryer (Curcuma domestica Valet) Using a Vacuum Oven - Zubaidi Achmad (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
Turmeric (Curcuma domestica Valet), known as Curcuma longa, is a type of spice that is well known among Indonesians. Turmeric contains a variety of compounds such as curcumin, which is sensitive to high temperatures. It is possible to conduct further research to improve drying outputs based on the curcumin concentration in turmeric. This study aims to establish the optimum conditions for drying turmeric (Curcuma Domestica Valet) in a vacuum oven with variable such as pressure, temperature, and drying duration. This study uses turmeric that has been peeled, rinsed, thinly sliced, and weighed around 15 grams before being tested for water content and initial curcumin content. The turmeric is dried in a vacuum oven, and after one hour the dried turmeric is weighed and its water content and curcumin contents are analyzed. Based on the results of this study, the optimum condition for drying in a vacuum oven are at a pressure of 0,5013 Atm with a water content of 71,78% and a curcumin content of 1,54%, as well as at a temperature of 70 oC with a water content of 33,20% and a curcumin content of 2,64%.